Structural dynamics of molybdenum vanadium oxide (MoVOx) - Suppiah, Durga Devi; Komar, A.; Hamid, Sharifah Bee Abd (Kluwer (now part of Springer), 2017)
Molybdenum and vanadium oxides were known to be an effective catalyst for light olefin (propane) activation for conversion to value-added chemicals. However, it is difficult to control the selectivity to desired product whereby subsequent reaction can lead to coking and rapid catalyst deactivation. One of the key ways to improve on the above limitation is to optimise and control the molybdenum phase structure, particularly during catalyst precursor activation stage. This paper demonstrates the combination of optimal in situ activation under different condition and thermal analysis for structural control that can help to guide and gain an insight into the structure–activity relationship of the nanostructured catalyst system. In situ XRD analysis reveals the crystallization of molybdenum vanadium oxide was highly influenced by the activation condition hence exhibiting different structural properties. Activation under Air at 300 °C forms highly crystalline hexagonal phase and transforms to thermodynamically stable orthorhombic (o-MoO3) phase at 450 °C. Activation under inert (helium) reveals the precursor remains amorphous until nanostructuring occurs at 450 °C. The precursor further transforms to the thermodynamically stable crystallized tetragonal phase (Mo5O14) at 500 °C. The obtained structural transition information is important in order to control and identify the catalytic active phase that is suitable for a particular reaction.